2005
DOI: 10.1007/s00415-005-0793-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of movement time in patients with essential tremor

Abstract: The simple test paradigm we have used showed that there is no difference in the movement time for repetitive movements around four joints of the upper extremity between patients with ET and normal control subjects. The slightly prolonged movement time around the shoulder joint noted in patients with ET may be ascribed to tremor, not bradykinesia. Tremor may cause these patients to pay more attention to the performance of goal-directed finger movements and consequently prolong movement time slightly or it may s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Comparisons with healthy subjects, as well as with the less affected side in ET patients themselves, demonstrated that ET was associated with decreased arm and leg frequencies, especially on the dominantly affected side of the body. These results are compatible with our previous study in which we showed some degree of prolonged movement time around the shoulder joint during repetitive movements in ET patients compared to age-matched controls [11]. In parallel, reviewing the video recordings, we observed that decreased associated arm movements were especially prominent in the proximal parts of the arms while walking, although not quantitatively measured.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Comparisons with healthy subjects, as well as with the less affected side in ET patients themselves, demonstrated that ET was associated with decreased arm and leg frequencies, especially on the dominantly affected side of the body. These results are compatible with our previous study in which we showed some degree of prolonged movement time around the shoulder joint during repetitive movements in ET patients compared to age-matched controls [11]. In parallel, reviewing the video recordings, we observed that decreased associated arm movements were especially prominent in the proximal parts of the arms while walking, although not quantitatively measured.…”
Section: Discussionsupporting
confidence: 92%
“…Slowness of movement during a fast wrist flexion/extension has been demonstrated in patients with ET with performance levels comparable to those of patients with mild PD [10]. In our previous study, we also showed that ET patients performed rapid alternating arm movements slower than those of controls, especially on proximal arm segments, though this difference was not significant [11]. Later, Duval et al [12] confirmed the presence of bradykinesia during rapidly alternating movement in ET patients and concluded that slow movements should be considered part of ET symptomatology.…”
Section: Introductionmentioning
confidence: 80%
“…Although several studies describe an abnormal olivo‐cerebellar network in ET,2–4 recent evidence suggests a neurodegenerative pathophysiology and even an overlap with Parkinson disease (PD). Indeed, ET is clinically progressive5 and several signs, such as bradykinesia,6–8 rest tremor,9 and hyposmia10–12 may be observed in ET. Moreover, a population‐based study revealed that patients with ET were four times more likely than unrelated healthy controls to develop incident PD 13.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the initiation of the movements of participants with ET was time-locked to the tremor circle, suggesting that not the execution itself, but the movement initiation is affected when performing rhythmic behavior. Support for this suggestion that the execution of rhythmic behavior is unaffected by ET has been provided by Ozekmekci et al (2005), who found that individuals with ET and controls did not perform differently a sequential-tapping task. Whereas the previous research suggested that initiation is largely unaffected in ET, other studies did show that both movement initiation and execution were affected (Montgomery, Baker, Lyons, & Koller, 2000;Jimenez-Jimenez et al, 2010).…”
mentioning
confidence: 85%